Eratosaster jenae ... - Mah, Christopher L. (Zenodo, 2011)
Eratosaster jenae nov. sp. (Figure 10 A–D) Diagnosis. Body strongly stellate. Abactinal plates strongly convex. Abactinal, marginal, and actinal plates bare and smooth with only peripheral granulation. Abactinal, marginal, and actinal plates with large conical spines. Furrow spines elongate, forming distinct spiny fringe on tube foot furrow. Subambulacral spine also elongate similar in size to furrow spines. Etymology. The genus is derived from the Greek Eratos for “lovely” and – aster for “star”. The species epithet, “ jenae ” is named for Dr. Jen Hammock, administrator of the US Antarctic Research Program, which has supported Antarctic biodiversity research and collections. Distribution. South Atlantic (Scotia Sea), Burdwood Bank. 339–1886 m. Material examined. HOLOTYPE: USNM 1149358 Burdwood Bank 54°42’S, 56° 36’ W, 339– 357 m. Coll. R/V Eltanin st. 1593, 14 March 1966 (1 dry spec. R=4.2, r=1.3). PARATYPES: USNM 1149359, Scotia Sea, SE of Burdwood Bank, off Falkland Islands 54°0’0”S, 55°53”W, 1879–1886 m. ... : Published as part of Mah, Christopher L., 2011, Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa, pp. 1-48 in Zootaxa 2759 on pages 24-25, DOI: 10.5281/zenodo.276783 ...